Digital Technology Integration for Climate Resilience In Coastal and Island Local Governance of Developing Countries: a Systematic Literature Review - Dina Dina; jamaliah Said (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2026)
Local governments in developing countries face mounting challenges from climate variability, particularly in coastal and island territories where conventional service-delivery mechanisms struggle to keep pace with emerging environmental risks. Digital technologies—geospatial systems, IoT sensing, remote sensing, and analytics platforms—offer pathways for strengthening local administrative and environmental-management capacity. This systematic literature review examines how integrated digital technologies are deployed to support climate resilience in coastal and island settings relevant to local governance across developing and emerging economies. Following PRISMA 2020 guidelines, a Scopus search retrieved 577 records (2023–2025); after title/abstract screening, 144 records underwent full-text eligibility assessment, and 35 studies meeting transparent inclusion criteria (HIGH methodological quality, integration of at least two technology types, and an explicit coastal or island setting) were included in the final qualitative synthesis. Rather than pooling heterogeneous outcomes into a single effect size, this review applies narrative synthesis and structured vote-counting, which is appropriate given the diversity of study designs, technologies, and outcome measures. The synthesis shows that technology integration clusters around four recurring patterns—IoT/sensors with remote sensing, AI/ML with digital platforms, remote sensing/GIS with data analytics, and digital platforms with analytics. Coastal settings dominate (25 of 35 studies) over island settings (10 of 35), and adaptation is the most common resilience focus (19 studies). The review identifies recurring enablers (geospatial monitoring capability, multi-source data integration) and persistent barriers (digital inequality, fragmented institutional data, and limited local technical capacity). The evidence base is descriptive and heterogeneous; findings should be read as patterns and directions rather than as pooled quantitative effects.